2021
DOI: 10.21203/rs.3.rs-373330/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nocturnal digital surveillance in aged populations and its effects on health, welfare and social care provision: a systematic review

Abstract: BackgroundThis systematic review summarized the effects of nocturnal digital surveillance technologies on health, welfare and social care provision outcomes in populations ≥ 50 years, compared to standard care.Primary studies published 2005-2020 that assessed these technologies were identified in 11 databases of peer-reviewed literature and numerous grey literature sources. Five publications out of 629 met inclusion criteria. The Risk of Bias 2.0 and ROBINS-I tools were used for quality assessment. ResultHealt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…The cameras also facilitated the eldercare personnel's work by making it easier for them to help each other across departments, prioritize, and create a better work environment. These findings contribute with information about the benefits of nocturnal digital surveillance technology, reducing the previous lack thereof [3,10]. The results from this study also make it possible to give useful feedback to the eldercare personnel.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The cameras also facilitated the eldercare personnel's work by making it easier for them to help each other across departments, prioritize, and create a better work environment. These findings contribute with information about the benefits of nocturnal digital surveillance technology, reducing the previous lack thereof [3,10]. The results from this study also make it possible to give useful feedback to the eldercare personnel.…”
Section: Discussionsupporting
confidence: 52%
“…This way of providing social care can increase the privacy and safety of older people. According to Richardson et al [10], there is a need for more high-quality intervention studies to gather evidence of the benefits of nocturnal digital surveillance technologies. Eldercare personnel experience lack of evidence of the benefits of the technology, although some projects have been running for a long time.…”
Section: Introductionmentioning
confidence: 99%
“…Recent systematic reviews show a lack of high-quality evidence for many expected effects of HWT that are broadly implemented in Sweden (19,20), and that expected or acceptable levels of value are not reached (21). Another recent systematic review of procurement practices in Sweden showed that requirements for, and assessment of, evidence for technologies' effectiveness is rarely used during the procurement process.…”
mentioning
confidence: 99%